Nutrient recovery from domestic effluent using an 2 indigenous strain of scenedesmus sp. - Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Buyong, Ramlah; Hashim, Nor Haslina; Matias-Peralta, Hazel Monica; Mohd-Kassim, Amir-Hashim (Wiley, 2018)
The performance of a Scenedesmus sp. in the phycoremediation of domestic 6 secondary effluents and the high-quality production of the effluents for safe 7 disposal are investigated in the current work. An indigenous strain of a 8 Scenedesmus sp. is obtained from a sludge thickness basin at a wastewater 9 treatment plant. The characteristics of this microalgae are identified using a 10 molecular analysis based on 18S ribosomal RNA sequences. The phycoremedia11 tion process is conducted in a photoreactor tank (5 L) with five different 12 concentrations of a Scenedesmus sp. (between 10 5 and 10 6 cells mL 1 ). The 13 reactors are then placed outdoors (exposed to natural environmental conditions) 14 for 8 days. The Scenedesmus sp. had the ability to remove 91.86%, 98.15%, and 15 93.11% of total nitrogen (TN), total phosphorus (TP), and total organic carbon 16 (TOC), respectively, and reduce biochemical oxygen demand (BOD), chemical 17 oxygen demand (COD), and total suspended solid (TSS) by 86.5%, 69.9%, and 18 76%, respectively, at a concentration of 10 6 cells mL 1 . Moreover, the increase in 19 the pH value during microalgae activity contributed to the increases in nutrients 20 and characteristics percentage removal. The treated secondary effluents gener21 ated from the phycoremediation process after 8 days met the EQA 1974 22 (Regulation 2009) sewage sludge (standard A) in terms of TN and TP but is still 23 not under the permissible limits for BOD, COD, and TSS. In conclusion, an 24 indigenous Scenedesmus sp. was efficient in enhancing the quality of secondary 25 wastewater to meet the standards required for reuse or safe disposal.